(untitled) (Psychology Travelogs, 2025)
During the last decade, solving the issue of preventing school violence has become one of the global social problems of society. In this context, it becomes important to search for factors and determine their role in the organization of a favorable educational environment in schools in Ukraine, to develop a methodology that contributes to the prevention of violence among schoolchildren based on mutual help and mutual respect. The purpose of the article is to substantiate the factors that can influence the eradication of bullying, mobbing and cyberbullying in the school environment of Ukraine. The methodological approach of the research is based on theoretical methods (comparative analysis, synthesis and generalization of theoretical data); empirical (questionnaires, testing, observations, surveys, heuristic conversation, dialogue, discussion, psychological and pedagogical trainings, seminars, debates); diagnostic (pedagogical observation and pedagogical experiment (diagnostic, formative, control). The content of the main concepts «bullying», «cyberbullying», «mobbing», «favorable educational environment» was determined; their signs and peculiarities were revealed, the method of creating a favorable environment was developed and implemented into the educational environment for the prevention of violence in schools of Ukraine. The outlined levels were assessed at high (5 points), medium (4 points) and low (1-3 points) levels. After conducting an experimental study, promising directions for improving the favorable educational environment in schools in Ukraine were formed. The practical value of the work lies in the development of methods of organization and implementation of a favorable educational environment in schools in Ukraine, which contributes to the eradication of bullying among students.